Reliability, validity and minimum clinical importance difference of the Chinese version of the Zurich claudication questionnaire - Yi-xuan Gao; Zhi-wen Weng; Hui Shao; Han Bo; Zhi-hui Chen; Meng Song; Lu-ping Liu; Ling-yun Zhang; Jia-yu Liu; Yu-han Wang; Meng-meng Zhang; Xi-you Wang; et al. (Scientific Reports)
Abstract The Zurich Claudication Questionnaire (ZCQ) has been translated and validated in multiple languages but few people have verified the measurement performance of the Chinese version of Zurich Claudication Questionnaire (Ch-ZCQ). The purpose of this study is to assess the performance of the Ch-ZCQ in lumbar spinal stenosis (LSS) patients undergoing non-surgical treatment. It includes the reliability, validity, responsiveness and minimally clinical important difference (MCID) of the two dimensions of symptom severity (SS) and physical function (PF). The results shows that the internal consistency and test-retest reliability were good. The content validity index was 0.764. The structural validity was good and moderate suitability. The correlation between the two dimensions of ZCQ is good, which is strongly correlated with Oswestry Disability Index (ODI) and moderately correlated with 12-item Short Form Health Survey Version 2(SF-12v2). Discriminative validity had significant differences in the degree of classification. The ZCQ’s SS and PF dimensions demonstrated a moderate Effect Size (ES) of 0.46 and 0.35. The Standardized Response Mean (SRM) was low, with values of 0.34 and 0.25. Additionally, the Change Rate (CR) was 10% for both, indicating a low level of change. MCID SS= -0.21[95% CI (-0.36, -0.05)]; MCID PF= -0.16[95% CI (-0.36, -0.03)]. This study demonstrates the Ch-ZCQ to be a reliable and valid tool, which can effectively evaluate the effectiveness of nonsurgical treatments for patients with LSS. However, to optimize its application for the Chinese population, further refinement is needed to address the ceiling/floor effects of some items.